O tratado de Andrea Pozzo e a pintura de perspectiva em Minas Gerais - Mateus Alves Silva (2012)
This work presents possible relations between the treaty of perspective drawing entitled Perspectiva Pictorum et Architectorum, by Andrea Pozzo, SJ (1642-1709) and pictorial production in Minas Gerais between the 18th and 19th century. Published in two volumes (1693 and 1700, respectively), Pozzos treaty allowed, through a didactic exposition method, a widespread learning of perspective drawing as well as the diffusion of a fondness for that kind of representation, being used countless times in the decoration of secular buildings and religious temples. In the latter ones, the painting technique simulating architecture was used to broaden and continue the internal space at the same time it marveled the audience with scenes of religious tradition. The captaincy of Minas Gerais would not escape the adoption of these decorations, producing the most representative perspective paintings in the Brazilian territory. As the paintings were directly or indirectly associated with the treaty, this work presents connections between them and possibilities of interpretation of the pictorial paintings, based on what was considered learned from or modeled by Andrea Pozzos treaty. The exposition is divided in two complementary parts: the analysis of both Perspectiva Pictorum et Architectorum volumes and its mechanisms of diffusion and circulation; and the examination of ceiling paintings of churches in Minas Gerais containing painted architecture as part of its internal decoration. Therefore, it was possible to establish the way in which the knowledge diffused by the work of Pozzo was made present, directly or indirectly, in the pictorial work of artists from the above mentioned period.